Daily functional electrical stimulation during everyday walking activities improves performance and satisfaction in children with unilateral spastic cerebral palsy: a randomized controlled trial - Pool, D.; Valentine, J.; Blackmore, A.; Colegate, J.; Bear, N.; Stannage, K.; Elliott, Catherine (2015)
Background: The aim of this paper is to determine whether daily functional electrical stimulation (FES) is effective in improving self-perceptions of individually identified mobility performance problems in children with unilateral spastic cerebral palsy (USCP). We hypothesized that children receiving 8 weeks of FES treatment would have higher scores for self-perceived performance and satisfaction on the Canadian Occupational Performance Measure (COPM) for individually identified priorities than children not receiving FES. Methods: Thirty-two children (mean age 10 y 8 mo SD 3y 3mo) with USCP and a Gross Motor Function Classification System I or II were randomly assigned to the FES treatment group (8 weeks of daily FES) and control group (usual treatments). Participants were assessed at baseline (week 0), post treatment (week 8) and 6 weeks follow-up (week 14). The primary outcome measures were self-perceived scores for performance and satisfaction of child- and parent-identified priorities assessed using the COPM post treatment and at follow-up. The secondary outcome measures were the categorization of the performance problems from the COPM and self-report responses according to the International Classification of Functioning Child and Youth version (ICF-CY). This was clinically important because an understanding of mobility performance problems for children with USCP is needed for family-centred service planning.Results: Performance scores (mean difference 1.6, 95 % CI 0.1 to 3.2, p = 0.034) and satisfaction scores post treatment (mean difference 2.4, 95 % CI 0.5 to 4.2, p = 0.004) were significantly higher in the treatment group than in the control group. There were no significant differences between the groups for performance scores at follow up, however there was a significant difference between the groups for satisfaction (mean difference 1.9, 95 % CI 0.1 to 3.8, p =  0.03) in favour of the treatment group. Priorities were identified across all levels of the ICF-CY but were most commonly identified in the activity and participation domains of the ICF-CY (79.5 %). Conclusions: Daily FES applied during everyday walking is effective in addressing self-perceptions of individually identified priorities by improving the performance and satisfaction of functional skills after treatment.